Sustaining women’s empowerment for development in resource-limited settings: an exploratory qualitative approach - Wallole, Wanno; Alano, Abraham; Endriyas, Misganu (Frontiers in Health Services, 2024)
BackgroundWomen's empowerment is one of the fundamental issues for attaining sustainable development goals crossing multiple dimensions. In Ethiopia, Women’s Development Network (WDN), a network of women, was established in 2010 with development aims. Ensuring women’s empowerment critically needs collective efforts of platforms such as WDN. However, there was a paucity of information about the patterns of WDN functionalities, its contribution, and factors affecting its functionality in rural areas of Southern Ethiopia. Hence, this study aimed to explore WDN status and factors affecting their functionality in Southern Ethiopia.MethodologyThe study employed an exploratory qualitative design. Data were collected from purposively selected zones using focus group discussions and key informant interviews. Audio-taped materials were transcribed verbatim and analyzed using a thematic approach. Initially, data were coded (open coding) and after several reviews, themes were developed and interpreted in line with the study objectives.ResultWDN has passed several steps from its establishment up to now. It was seen skeptically at its early inception, very good level of acceptance in the middle, and staggering currently. However, WDN has contributed to improvements in household welfare resulting from increased ability to afford food, clothing, health, and education. Specific to health, WDN has contributed to general awareness creation, maternal and child health utilization, and environmental sanitation. On the other hand, the volunteer nature of the job put pressure on WDN and revealed socioeconomic stresses. Moreover, inconsistent support from stakeholders especially health extension workers, inadequate men’s engagement, and sidelining of WDN by some educated women remain challenges for the sustainable functionality.ConclusionWDN has contributed to multidimensional development goals, especially health services uptake and environmental sanitation. However, over time, it became flaccid and lost adequate emphasis from most of its stakeholders and supportive structures. Therefore, considering such vital inputs from community participation in resource-limited settings, stakeholders should offer adequate attention to WDN in terms of selection, training, orientation, follow-up, and acquainting with the community they serve. Moreover, efforts are needed to retain women voluntarily serving and build positive images across all stakeholders and fellow women receiving the services.